The Mediating Effect of Specific Social Anxiety Facets on Body Checking and Avoidance - Radix, Anne Kathrin; Rinck, Mike; Becker, Eni Sabine; Legenbauer, Tanja (Frontiers in Psychology, 2019)
Objective: Body checking (BC) and avoidance (BA) form the behavioral component of body image disturbance. High levels of BC/BA have often been documented to hold a positive and potentially reinforcing relationship with eating pathology. While some researchers hypothesize, that patients engage in BC/BA to prevent or reduce levels of anxiety, little is known about the mediating factors. Considering the great comorbidity between eating disorders (ED) and in particular social anxieties, the present study investigated whether socially relevant types of anxiety mediate the relationship between eating pathology and BC/BA. Methods: 83 participants reporting an eating disorder and 323 healthy participants (14–25 years) took part in an online survey. Eating pathology was measured with the Eating Disorder Examination Questionnaire and Body Checking and Avoidance Questionnaire. Trait and social anxiety were assessed by means of the State Trait Anxiety Inventory (STAI-T), the Fear of Negative Evaluation (FNE) and the Social Appearance and Anxiety Scale (SAAS). Separate mediation analyses were carried out with eating pathology as independent variable, BC/BA as dependent variable and STAI, FNE, and SAAS as mediating variables. Results: Anxieties correlated highly positive with eating pathology in both groups. SAAS mediated the relationship between ED pathology and BC/BA in participants with ED and mediated the relationship between ED pathology and BA in healthy participants. FNE mediated the relationship between eating pathology and BA for participants with eating pathology. Discussion: SAAS mediated the relationship between eating pathology and BC/BA. Being afraid of bodily evaluations may represent a particular relevant fear that triggers safety behaviors.